Smart nanocarrier based on PEGylated hyaluronic acid for deacetyl mycoepoxydience: High stability with enhanced bioavailability and efficiency. (1st January 2019) - Zhao, Juan; Wang, Yancai; Ma, Yingying; Liu, Yangyang; Yan, Beibei; Wang, Lulu
Highlights: A core-shelled structure drug delivery system was designed. The DM nanocrystals core was prepared by anti-solvent precipitation method. PEG-HA shell possesses pH-responsible ability of release drug in suitable position. TPGS and DSPE-PEG-FA as functional stabilizers for stable nanocrystals. Response surface methodology for select optimum DM nanosuspensions formulation. Abstract: Deacetyl mycoepoxydience (DM) nanocrystals core were stabilized by the folate modified distearoylphosphatidyl ethanolamine-polyethylene glycol (DSPE-PEG2000 -FA) as the active-targeting stabilizer and D-α-tocopherol polyethylene glycol 1000 succinate (TPGS) as the reversion of multidrug resistance stabilizer, respectively. The DM nanocrystals was acted as the core and shelled by the polyethylene glycol-hyaluronic acid (PEG-HA). The optimal core-shell system demonstrated superior stability at 4 °C for 6 weeks by the stability study and higher dissolution velocity. Cytotoxicity in vitro and cell proliferation inhibition was evaluated by MCF-7 cells line. Furthermore, the core-shell nanocrystals revealed a concentration- and time-dependent cytotoxicity activity and enhanced the cell proliferation inhibition. Pharmacokinetic studies in rabbits showed core-shelled DM nanocrystals significantly increased AUC and t1/2 and reduced CLz compared to the DM solution for intravenous delivery. Results indicated that core-shell nanocrystals nanogel was successfully established with higher stability and the bioavailability of DM with higher safety was improved.